Atrial fibrillation is a risk factor for major adverse cardiovascular events in COVID-19. (December 2022) - Cutler, Michael J.; May, Heidi T.; Bair, Tami L.; Crandall, Brian G.; Osborn, Jeffrey S.; Miller, Jared D.; Mallender, Charles D.; Muhlestein, Joseph B.; Anderson, Jeffrey L.; Knowlton, Kirk U.; Knight, Stacey
Abstract: Background: New-onset atrial fibrillation (AF) during COVID-19 infection is associated with worse cardiovascular outcomes and mortality, with new-onset AF being associated with worse clinical outcomes than recurrent AF. However, it is not known whether a prior history of AF is an independent cardiovascular risk factor predicting worse outcomes in COVID-19 patients. The present investigation sought to determine whether AF should be considered a risk factor for worse outcomes in COVID-19 illness. Methods: From March 2020-September 2021 patients testing positive for SARS-CoV-2 with a prior AF diagnosis (n = 3623) were propensity matched to non-AF SARS-CoV-2 positive patients (n = 3610). Multivariable Cox hazard regression was used to determine subsequent MACE (all-cause death, myocardial infarction, HF and stroke) risk among patients with and without AF. Results: COVID-19 patients with a prior history of AF were more likely to be hospitalized, require ICU care, supplemental oxygen, and ventilator support compared COVID-19 patients without a history of AF. There was a 1.40 times higher rate of MACE in the COVID-19 patients with prior AF compared to patients without prior AF ( p < 0.0001). The increased rate of MACE in patients with a prior AF was primarily secondary to increases in heart failure hospitalization and death. This finding was confirmed even after controlling for acute AF during COVID-19 illness (HR 1.22, p = 0.0009). Conclusion: AF history was shown to be an independent risk factor for MACE during a COVID-19 illness. Both recurrent and principally new-onset AF were associated with an increased risk of poor clinical outcomes during COVID-19 illness.